Best Answer

Not sure why it is 3a2- if you mean 3*a*2, then:


(6a-2a)+5-2(a (or a2)+a)=1



Then take the 5 over (remember, the +5 become -5 when transposed):


Solving the equations on both sides gives:


Is this your answer?

User Avatar

Wiki User

โˆ™ 2011-02-24 16:16:05
This answer is:
User Avatar

Add your answer:

Earn +20 pts
Q: When 3a2-2a plus 5 subtracted by a2 plus a equals 1?
Write your answer...
Related questions

When a2 plus a-3 is subtracted from 3a2-5 the answer is?

5a+3a2a2= 8a a2

If a2 plus b2 equals c2 then c2 equals b2 equals?


Why is the Pythagorean therm a2 plus b2 equals c2 not a plus b equals c?

l a2 b2 is c2!!Its completely norma

A2 plus 3 equals 12?


If 2 plus 3 equals 10and 7 plus 2 equals 63and 6 plus 5 equals 66and 8 plus 4 equals 96 then 9 plus 7 equals?

144 Formula: c= (a2)+(ab)

If a2 plus b2 equals c2 then the triangle is?

a right triangle

A2 plus b2 equals c2 is an example of?

Pythagorean Theorem

Solve a2 plus 30a plus 56 equals 0?

a2+30a+56=0 , solve for a Using the quadratic formula, you will find that: a=-2 , a=-28

What is the algebraic formula for a2 plus b2 equals c2?

You just typed it.

If a plus b plus c equals x plus y plus z then prove a2 plus b2 plus c2 equals x2 plus y2 plus z2?

a2+b2+c2=x2+y2+z2 divide each side by 2 (a2+b2+c2)/2=(x2+y2+z2)/2 a+b+c=x+y+z

What does a2 plus ab equals h2 mean?

It is an expression and a term that are of equal value

What should be subtracted from a2 -4a2 plus 5a2-6 to obatain a2-2a plus 1?

If I've read your question correctly, you need to subtract: a2 +2a -7 a2 -4a2 +5a2 -6 = 2a2 -6 Note, if x - y = z, then y = x - z; so: 2a2 -6 - (a2 -2a +1) = 2a2 -6 - a2 +2a -1 = a2 +2a -7

Who introduced a2 plus b2 equals c2?

Pythagoras' theorem for a right angle triangle.

What are the lengths of and A plus B in a right triangle if C equals 8?

A2 + B2 = C2 If C=8, then A2 + B2 = 64

How do you factor polynomial a4 plus a2?

( a2 ) ( a2+1 )

CosA equals a2 plus c2 minus b2 by 2ac what is this formula?

This is known as the Cosine Rule.

What is the answer to a squared plus -5a squared - a squared - a?

a2 + -5a2 - a2 - a = a2 - 5a2 - a2 - a = a2 - 6a2 - a = -5a2 - a

Factor A2 plus 4a plus 4 - b2?

a2 - 4a + 4

Math inventor of a2 plus b2 equals c2?

Pythagoras. That's why it's called the Pythagorean Theorem.

What is A squared plus 6 squared equals 12 squared?

a2 + 62 = 122 a2 + 62 - 62 = 122 - 62 a2 = 144 - 36 a2 = 108 taking the square root of each side, we get a equal plus or minus the square root of 108, or plus or minus 6 times the square root of 3.

How do you simplify 5-a-1 plus c-6a2 plus a2?

5 - a - 1 + c - 6a2 + a2

What is the first and second derivative of R equals q2 plus 3qa plus a2?

Rprime= 2q + 2a + 3 Rdoubleprime= 4

What does a squared plus a squared equal?

a2 + a2 = 2a2

What is the factor of a2 plus 9a plus 20?

a2+9a+20 = (a+4)(a+5) when factored

How do you calucate a2 plus b2?


Study guides

Create a Study Guide